DESAIN DAN REALISASI MODEL PEMBANGKIT LISTRIK TENAGA SAPI - , Muhammad Sholikhin, Ir. Samsul Kamal, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In Indonesia, there are many sources of alternative energy that can be converted into electrical energy, such as cow power. Generally, there are two commonly used profits from cow, it is the energy used to plow their fields, transporting goods and its waste can be make biogas, fertilizer and electricity. Use of cow dung was mostly done, while the new limited utilization of cattle to plow rice fields. In this research, cow power conversion into electricity is done by cow make a circular motion to rotate a generator through the transmission system. To get a high ratio from 3 rpm to 1500 rpm be able to change the electric motor becomes a generator. Besides on the transmission needed to reach four levels. Cow Power Plant system performanceâs as a whole is done by connecting the mechanical system of cows with a generator through the transmission system. Generator is used in the form of an induction generator with a capacity of 1 / 4 Hp, Ns = 1500 rpm, 50 Hz, 3 Phase, 380/220 Volt. In the test, it is carried out with a cow and a load generator is load lamp which is expression of the real power with cos Ï = 1. The highest system efficiency is obtained at a load 45 watts with Î· = 27%. Utilization of the system at night is used for lighting the house during the 6-10 hours. With electricity previously stored in battery at the cow work during the day.